2022
DOI: 10.1093/humrep/deac174
|View full text |Cite
|
Sign up to set email alerts
|

‘I’m the only mum she knows’: parents’ understanding of, and feelings about, identity-release egg donation

Abstract: STUDY QUESTION How do parents understand and feel about identity-release egg donation? SUMMARY ANSWER Almost one-third of mothers and fathers did not understand the identifiable nature of their egg donation; mothers expressed complex and sometimes difficult feelings about the prospect of future donor–child contact. WHAT IS KNOWN ALREADY Identity-release egg d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…At Phase 1 of the study, mothers and infants in egg donation families had shown less optimal interaction quality (Imrie, Jadva, Fishel, & Golombok, 2019), a difference that may be explained by some mothers in egg donation families finding it challenging to adjust to nongenetic parenthood, perhaps because of a lack of physical resemblance with their child. In the present phase of the study, some mothers reported that knowing what the donor looked like might interfere their relationship with their child (Lysons et al, 2022, 2023). However, no differences were identified between family types on the observational measure of interaction quality.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…At Phase 1 of the study, mothers and infants in egg donation families had shown less optimal interaction quality (Imrie, Jadva, Fishel, & Golombok, 2019), a difference that may be explained by some mothers in egg donation families finding it challenging to adjust to nongenetic parenthood, perhaps because of a lack of physical resemblance with their child. In the present phase of the study, some mothers reported that knowing what the donor looked like might interfere their relationship with their child (Lysons et al, 2022, 2023). However, no differences were identified between family types on the observational measure of interaction quality.…”
Section: Discussionmentioning
confidence: 78%
“…Identity-release donation is not without its challenges. The prospect of the child learning the donor's identity in the future and potentially being able to contact them may be threatening for some parents and offer less clear boundaries between the two families (Lysons et al, 2022(Lysons et al, , 2023. The process of deciding whether and how to disclose the child's donor conception to them may also pose different challenges in identity-release families, as disclosure may have a different meaning to parents, given that the child may discover the donor's identity in the future (Isaksson et al, 2016) which may add greater complexity to these decisions (Freeman et al, 2016).…”
mentioning
confidence: 99%
“…It is perhaps not surprising that the egg donation mothers, who lacked a genetic connection to their children, obtained higher scores on this measure than the sperm donation mothers, who did not. In the recent study of mothers of children born using an identifiable egg donor, some mothers reported anxiety during pregnancy about whether they would bond with their baby (Imrie et al, 2020), and when the children reached age five, some perceived their child's ability to access the donor's identity as a direct threat to their relationship with their child, and to their identity as their child's mother (Lysons et al, 2022). Egg donation mothers' ratings of less positive family relationships are notable given the absence of separated or divorced egg donation mothers in the present phase of the study, perhaps reflecting a tendency for mothers who do not have a genetic tie to their children to remain with their children's father even when experiencing an unsatisfactory marriage.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of families created using identifiable egg donors by the present research team, found that many mothers were concerned during pregnancy that they would not bond with their baby, and although most felt that the baby was their own by age 1, some still struggled with the idea that their child was not genetically related to them (Imrie et al, 2020). When followed up at age 5, some mothers reported feeling threatened by the prospect of their child discovering the identity of the egg donor, and possibly forming a relationship with her (Lysons et al, 2022). These reactions are perhaps unsurprising given the high level of social significance that is placed upon genetic connections (Freeman, 2014; Groll, 2021).…”
Section: Absence Of Biological Connections and Child Adjustment Problemsmentioning
confidence: 99%
“…Secondly, this suggests that, at the point of choosing a donor, intended parents need to be provided with comprehensive, accessible information, by agencies and clinics, to help all parents make informed decisions, and to assist parents to better understand the implications of different types of gamete donation. Research by Lysons et al (2022) revealed that parents of 5-year-old children who used identifiable donation sometimes did not show a full understanding of the type of egg donation they had used. The present research further emphasizes the importance of enabling parents to be fully informed in their decisions when using donated gametes.…”
Section: Discussionmentioning
confidence: 99%